The effect of analog-to-digital (ADC) resolution on the performance of millimeter wave (mmW) communication system - Ang, Kar Leong (Nanyang Technological University, 2020)
This reports aims at investigating the bit error rate (BER) performance of using the hybrid beamforming architecture for mmWave beamforming. It also investigates the possibilities of compromising the resolution of converters (source of much of the power consumption of the system) in hybrid mmWave MIMO system based on BER performance to determine the feasibility to further reduce cost from the converters.